The impact of emerging technologies on work: a review of the evidence and implications for the human resource function [version 1; peer review: 2 approved, 1 approved with reservations] - Emma Parry; Valentina Battista (Emerald Publishing, 2019)
Popular media suggests that technological advancement will continue to have a dramatic effect on work, but it is difficult to distinguish between the hype surrounding this and the actual potential impacts. This study examines what the evidence is in relation to the impact of emerging technologies on work and the role of the human resource (HR) function in helping employees and organisations to navigate these changes.  Evidence suggests that the latest technologies, such as artificial intelligence and robotics, are being employed by organisations to automate simple and repetitive tasks as well as to make complex decisions quickly and more accurately via predictive algorithms. In addition, emerging technologies are increasingly being used to support the implementation of more flexible working practices such as virtual work and gig work. However, this will present a number of challenges for HR professionals, who will need to help employees to update their skills to compete in the future world of work, and to find ways to address the possible negative effects of increased connectivity and precarious working arrangements on employee wellbeing.